2012
DOI: 10.1016/j.jhep.2012.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte-like cells differentiated from human induced pluripotent stem cells (iHLCs) are permissive to hepatitis C virus (HCV) infection: HCV study gets personal

Abstract: Human pathogens impact patient health through a complex interplay with the host, but models to study the role of host genetics in this process are limited. Human induced pluripotent stem cells (iPSCs) offer the ability to produce host-specific differentiated cells and thus have the potential to transform the study of infectious disease; however, no iPSC models of infectious disease have been described. Here we report that hepatocyte-like cells derived from iPSCs support the entire life cycle of hepatitis C vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Another in vitro application will be for the study of hepatitis infection and disease. Recently it has been shown that both mouse and human iPS-derived hepatocytes are capable of HCV infection and replication (Aly et al 2011; Yoshida et al 2011; Si-Tayeb et al 2012). …”
Section: Alternative Models To Primary Human Hepatocytesmentioning
confidence: 99%
“…Another in vitro application will be for the study of hepatitis infection and disease. Recently it has been shown that both mouse and human iPS-derived hepatocytes are capable of HCV infection and replication (Aly et al 2011; Yoshida et al 2011; Si-Tayeb et al 2012). …”
Section: Alternative Models To Primary Human Hepatocytesmentioning
confidence: 99%
“…In the case of hESCs the risk of contamination of the original donor tissue with the most serious blood-borne pathogens is very low ( Zou et al , 2004 ). However, when stem cell lines are differentiated to form tissue cell types they may provide a suitable culture substrate for the growth of pathogenic viruses such as HCV, HBV ( Si-Tayeb et al , 2012 ) and other pathogens depending on the cell types generated ( Bandi and Akkina, 2008 ). Thus, when planning experiments to provide a particular differentiated cell type, consideration should be given to the most likely contaminants that may arise in reagents, cells and any test samples that might replicate in the differentiated cell types.…”
Section: Cell Line Practicementioning
confidence: 99%
“…Stem cell derived hepatocytes have also become invaluable for use in modelling infectious diseases such as hepatitis C virus (HCV) infection [93][94][95] and malaria in order to establish effective systems to investigate disease progression and assays for drug screening. Various groups [33,96] employed the use of hiPSC-HEPs in investigating HCV infection.…”
Section: Applications Of Hipsc-hepsmentioning
confidence: 99%